Single QTL Effects, Epistasis, and Pleiotropy Account for Two-thirds of the Phenotypic F2 Variance of Growth and Obesity in DU6i x DBA/2 Mice - Brockmann, Gudrun A.; Kratzsch, Jürgen; Haley, Chris S.; Renne, Ulla; Schwerin, Manfred; Karle, Steffanie (Genome Research, 2000)
Genes influencing body weight and composition and serum concentrations of leptin, insulin, and insulin-like growth factor I (IGF-I) in nonfasting animals were mapped in an intercross of the extreme high-growth mouse line DU6i and the inbred line DBA/2. Significant loci with major effects (F > 7.07) for body weight, obesity, and muscle weight were found on chromosomes 1, 4, 5, 7, 11, 12, 13, and 17, for leptin on chromosome 14, for insulin on chromosome 4, and for IGF-I on chromosome 10 at the Igf1 gene locus itself and on chromosome 18. Significant interaction between different quantitative trait loci (QTL) positions was observed (P < 0.01). Evidence was found that loci having small direct effect on growth or obesity contribute to the obese phenotype by gene–gene interaction. The effects of QTLs, epistasis, and pleiotropy account for 64% and 63% of the phenotypic variance of body weight and fat accumulation and for over 32% of muscle weight and serum concentrations of leptin, and IGF-I in the F2 population of DU6i x DBA/2 mice.[The quantitative trait loci described in this paper have been submitted to the Mouse Genome Database.]
10.1101/gr.149900